2009
DOI: 10.2337/dc09-1503
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Perspectives on Type 1 Diabetes in Childhood and Adolescence in Germany

Abstract: OBJECTIVETo predict the frequency of type 1 diabetes in childhood and adolescence (<15 years of age) in Germany for the next 20 years.RESEARCH DESIGN AND METHODSData on diabetes onset has been collected by means of a registry in the federal German state of Baden-Württemberg (documentation period, 1987–2006; n = 5,108; completeness of data 98.1%).RESULTSThe current incidence rate (2000–2006) is 19.4 per 100,000 per year (95% CI 18.6–20.2). The annual incidence rate can be expressed as a square of a linear funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 13 publications
2
34
1
2
Order By: Relevance
“…Two youngest age groups (0-4 and 5-9 years) had the highest relative increase. This is in accordance with other studies reporting the increasing incidence of T1DM mostly in younger age group [11][12][13][14] , but is completely different from data reported in Croatia where the increase in the disease incidence ceased in the youngest children 15 . Similar to some other studies 16,17 , we found a steep increase in the incidence T1DM in Montenegro boys under five years of age.…”
Section: Discussionsupporting
confidence: 45%
“…Two youngest age groups (0-4 and 5-9 years) had the highest relative increase. This is in accordance with other studies reporting the increasing incidence of T1DM mostly in younger age group [11][12][13][14] , but is completely different from data reported in Croatia where the increase in the disease incidence ceased in the youngest children 15 . Similar to some other studies 16,17 , we found a steep increase in the incidence T1DM in Montenegro boys under five years of age.…”
Section: Discussionsupporting
confidence: 45%
“…The incidence of T1DM has significantly increased worldwide [2][3][4][5][6][7] and environmental factors are thought to play a critical role in this. Innate immunity protects hosts from bacterial invasion by recognizing bacterial components through their pattern recognition receptors (PRRs).…”
Section: Introductionmentioning
confidence: 99%
“…Over time, b-cell destruction results in insulin deficiency, worsening hyperglycemia and an eventual call for insulin therapy. As the incidence of T1D is increasing at a rate far beyond the rate of population growth, additional emphasis has been placed on the contribution of environmental factors towards disease onset (Ehehalt et al, 2010;Patterson et al, 2001;Vaarala et al, 2008). Indeed, the intestinal microbiota is an environmental factor that cannot be overlooked as a contributor towards T1D development or a factor that is significantly altered as a result of T1D development.…”
Section: Introductionmentioning
confidence: 99%